Da narração à montagem: a linguagem cinematográfica em questão - Lourenço, Lucas Bandos (2020)
This work aims to investigate the montage procedure, as well as its contributions to the constitution of the cinematographic language, which acquires a new role, as it faces the new cultural reality forged by the modernist movements. With the advancement of artistic avant-garde, already in the early years of the twentieth century, the newly emerged cinema needs to find for itself another dramatic environment, capable not only of overcoming the atmosphere of private life, but of embracing the wide technical, political and socioeconomic transformations imposed by the industrial revolution, as well as by the saturation of advanced capitalism. It is in this environment that the city appears not only as a scenario, but as the ideal protagonist of a new reality. This reality permeates the most diverse forms of artistic expression, among which cinema itself, which finds in the montage method, proposed by the Russian director Sergei Eisenstein, the appropriate procedure to reconfigure itself, both from the aesthetic and ideological point of view. Conceived by Eisenstein (2000) as a basic and primordial element of film language, the montage serves here as a starting point for a deeper understanding not only of modernity as an inherently cinematographic experience, as proposed by Charney and Schwartz (2004), but also of cinema as an element that both founds itself in the city and reflects it imagery, as suggested by Wenders (1994). Tracing a panorama that ranges from the first short films of the one that Gunning (1995) called “cinema of attractions” to the avant-garde Soviet films, we seek to understand cinematographic language not as a product or consequence, but as an intrinsic part of modern urban culture, in the midst of which it appears not as a mere supporting factor, but as a co-creative agent